THE INTEGRATION OF RAISSONDâETRE AND SOCIAL LINKAGE (RISOL) PROGRAM AS A FINANCIAL LITERACY EDUCATION MODEL - -, Fahmi Ulin NiÃ¢Â€Â™mah - (Prosiding Seminar Pendidikan Ekonomi dan Bisnis, 2017)
ABSTRACTFinancial literacy is knowledge and understanding important to posses by an individual. Financial understanding will help an individual manage his/her finance. The importance of financial literacy has been realized in many countries. In Indonesia, Financial Service Authority (thereafter called OJK) has conducted socialization and education intensely about financial literacy to society. The learning at college plays an important role in the process of creating the studentsâ financial literacy. Diverse and complex economic environment affects decision making concerning finance. Financial literacy education should be developed in college programs to generate the studentsâ awareness of the importance of finance literacy to support their life in workplace or business realm. Education models that have been designed in foreign countries are Raisson Dâetre and social capital programs. This article addressed the financial literacy education model that can be adopted in Indonesia using literature study research method. The financial literacy education model that can be adopted in Indonesia, particularly at college level, is the integration of Raisson Dâetre and social linkage (RISOL) program. The education model developed with the program starting from curriculum and assessment by utilizing surrounding environment and cooperation with financial institutions in Indonesia.Â Keywords: Financial Literacy, Raisson Dâetre, Social Linkage, education model ABSTRAKLiterasi keuangan merupakan pengetahuan dan pemahaman yang penting untuk dimiliki seseorang. Pemahaman akan keuangan akan membantu seseorang dalam mengelola keuangannya. Pentingnya literasi keuangan sudah disadari berbagai negara, di Indonesia Otoritas Jasa Keuangan telah gencar melakukan sosialisasi dan edukasi literasi keuangan pada masyarakat. Pembelajaran di perguruan tinggi memiliki peran penting dalam proses pembentukan literasi keuangan mahasiswa. Lingkungan ekonomi yang beragam dan kompleks memberikan banyak pengaruh pada pengambilan keputusan yang menyangkut keuangan.Pendidikan literasi keuangan perlu dikembangkan dalam program-program di perguruan tinggi untuk menanamkan bahwa pemahaman tentang keuangan penting untuk penunjang kehidupannya setelah terjun ke dunia kerja maupun dunia usaha.Model edukasi yang telah dirancang di luar negeri adalah program Raisson Dâetre dan sosial capital.Â Artikel ini akan membahas tentang model edukasi literasi keuangan yang dapat diadopsi diÂ Indonesia dengan metode penelitian studi literatur. Model edukasi literasi keuangan yang dapat diadopsi di Indonesia khususnya untuk tingkat pergururan tinggi adalah program integrasi raisson dâetre dan social linkage (RISOL).Model edukasi yang dikembangkan dengan program mulia dari kurikulum dan penilaian dengan memanfaatkan lingkungan sekitar serta bekerjasama dengan lembaga-lembaga keuangan di Indonesia.Keywords: Literasi Keuangan, Raisson Dâetre, Social Linkage, model edukasi